2023
DOI: 10.1038/s41598-023-32581-w
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in post-exercise fatigue and function in myalgic encephalomyelitis/chronic fatigue syndrome

Abstract: To assess biobehavioral sex differences in myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) utilizing a low burden exercise protocol, 22 females and 15 males with ME/CFS and 14 healthy controls underwent two six-min walk tests. Fifteen daily assessments were scheduled for fatigue and function ratings and heart monitoring. Six-min walk tests were conducted on days 8 and 9. The ME/CFS group showed high self-report fatigue and impaired physical function, whereas healthy controls did not show fatigue or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Other studies found that women more often had PEM and OI than men ( 11 , 14 ). As this was confirmed in our study population for PEM, subsequent analyses were stratified by sex.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Other studies found that women more often had PEM and OI than men ( 11 , 14 ). As this was confirmed in our study population for PEM, subsequent analyses were stratified by sex.…”
Section: Methodsmentioning
confidence: 89%
“…PEM refers to the abnormal worsening of various symptoms (which can be fatigue) and loss of energy following minimal physical or cognitive stressors or other triggers that would have been tolerated normally before disease onset ( 6 ). PEM has been found to be more prevalent in women than in men ( 11 ), and infections can initiate PEM ( 12 ). Another comorbidity with ME/CFS is postural orthostatic tachycardia syndrome (POTS), which generally causes orthostatic intolerance ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another key limitation is that we only included females. While the majority of ME/CFS patients are female, there are also male patients and it cannot be assumed that these results would apply to males as well, as many sex differences have been documented (Friedberg et al., 2023 ; Germain et al., 2022 ). A third limitation is that this study is limited to patients that were physically able to complete the exercise protocol, so the most severe and disabled ME/CFS patients are not represented in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Both maximal and submaximal exercise protocols have been used to determine behavioral and physiological consequences of acute exercise challenge in illnesses such as GWI, ME/CFS and long coronavirus disease [ 25 , 71 , 107 111 ]. Here we used exercise challenge to explore the consequences on GWI with and without PTSD symptomatology.…”
Section: Discussionmentioning
confidence: 99%